Positive time use: a missing link between time perspective, time management, and well-being - Osin, Evgeny; Boniwell, Ilona (Frontiers in Psychology, 2024)
Introduction The notion of satisfaction with the use of one’s time has not been operationalized previously. Based on qualitative interviews, we propose a concept of positive time use comprised by four components: self-congruence of daily activities, balance between activities, efficient use of time, and a sense of mastery over one’s time. Methods Using data from two UK adult samples (N = 173 and N = 357), we developed a new measure, Positive Time Use Inventory (PTUI), and investigated its structural and convergent validity. Results and discussion The associations of positive time use with balanced time perspective, affect balance, satisfaction with life, sense of coherence, and self-reported satisfaction with time use indicate convergent and discriminant validity of the new measure. Positive time use partially explained the associations of balanced time perspective with subjective well-being and fully mediated the effects of future time perspective and time management on subjective well-being. We propose positive time use as a new model of temporal well-being, which brings together the notions of work-life balance, time efficiency, and time mastery in a single comprehensive framework, helping to inform the time management coaching interventions.